2010
DOI: 10.3109/14992020903160892
|View full text |Cite
|
Sign up to set email alerts
|

Multi-site diagnosis and management of 260 patients with Auditory Neuropathy/Dys-synchrony (Auditory Neuropathy Spectrum Disorder*)

Abstract: Test results and management data are summarized for 260 patients with diagnoses of Auditory Neuropathy Spectrum Disorder (ANSD). Hearing aids were tried in 85 of these patients, and 49 patients tried cochlear implants. Approximately 15% reported some benefit from hearing aids for language learning, while improvement in speech comprehension and language acquisition was reported in 85% of patients who were implanted. Approximately 5% (13/260) of the total population developed normal speech and language without i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
256
4
19

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 268 publications
(294 citation statements)
references
References 66 publications
15
256
4
19
Order By: Relevance
“…Two separate Nigerian studies indicated a prevalence of 4.9% in a sample of children diagnosed with SNHL [45] and 13.5% in a cohort of children with severe-profound hearing loss [44]. Hyperbilirubinemia has been associated as the most commonly reported risk factor for ANSD, varying between 30 to 70% [38,[46][47][48]. The current study had 50% of ANSD cases presenting with hyperbilirubinemia as a risk factor similar to a recent report from South Africa in which half of the ANSD cases (n=5/10) also presented with hyperbilirubinemia [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two separate Nigerian studies indicated a prevalence of 4.9% in a sample of children diagnosed with SNHL [45] and 13.5% in a cohort of children with severe-profound hearing loss [44]. Hyperbilirubinemia has been associated as the most commonly reported risk factor for ANSD, varying between 30 to 70% [38,[46][47][48]. The current study had 50% of ANSD cases presenting with hyperbilirubinemia as a risk factor similar to a recent report from South Africa in which half of the ANSD cases (n=5/10) also presented with hyperbilirubinemia [24].…”
Section: Discussionmentioning
confidence: 99%
“…For the capturing of pre-operative behavioral pure tone and Auditory Steady State Response (ASSR) threshold data, when a "no response" was indicated in the clinical file at a respective frequency, the threshold was captured as 120 dBHL. The minimum diagnostic criteria considered for ANSD were the presence of otoacoustic emissions and/or a response for a cochlear microphonic between 80 and 90 dB nHL, with the absence of or severely abnormal Auditory Brainstem Response (ABR) waves [38].…”
Section: A Commercially Available Statistical Software Package (Ibm Smentioning
confidence: 99%
“…Hearing impaired listeners often manifest auditory neuropathy as a difficulty understanding speech (Zeng et al 1999), or in the case of young children, as a delayed acquisition of speech (Berlin et al 2010). Given the dynamic acoustic properties of speech, it is not surprising that this complex perceptual behavior would be compromised by the type of functional deficits that are evident in the auditory nerve and cochlear nucleus of noise-reared α9KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty percent of infants with admission RR AABR converted to bilateral pass, whereas 22 infants had persistent RR AABR confirmed to be auditory neuropathy by diagnostic audiology procedures. [17][18][19] All infants with maximum TSB ,31 mg/dL and BIND score #3 had normal auditory function at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A diagnostic evaluation for auditory neuropathy [17][18][19] was performed if the AABR screen was RR at 3 to 5 months. Compliance with follow-up appointments was 74.5%.…”
Section: Outcome Definitionsmentioning
confidence: 99%